Acylcarnitine profiles of preterm infants over the first four weeks of life - Meyburg, Jochen; Schulze, Andreas; Kohlmüller, Dirk; Pöschl, Johannes; Linderkamp, Otwin; Hoffmann, Georg F.; Mayatepek, Ertan (Pediatric research, 2002)
Measurement of free carnitine and acylcarnitines allows the detection of several inborn errors of metabolism in neonatal screening. Because available data for premature infants is limited, we studied longitudinal changes in acylcarnitine profiles of full-term and preterm neonates over the first 4 weeks of life. One hundred twenty infants were divided into four groups of 30: A, gestational age 22 to 27 wk; B, 28 to 31 wk; C, 32 to 36 wk; and D, 37 to 41 wk. Blood samples spotted on a Guthrie card were taken on days 5 and 28. Additional specimens (groups A and B only) were collected on days 1, 3, 7, and 14. Carnitine and its acyl esters were detected by looking for the precursor ions of m/z = 85 using a PE Sciex API 365 electrospray ionization tandem mass spectrometer. Concentrations of free carnitine and most acylcarnitines were significantly higher in group A compared with group D postnatally. Groups B and C displayed intermediate values. Carnitine levels in infants from group A and B decreased steadily from day 1 to day 7, and recovered up to day 14 in group B only. On day 28 carnitine concentrations had further decreased in group A, while reaching postnatal levels again in group B. Postnatal carnitine levels are higher in very immature preterm infants compared with full-term infants, but become lower on day 28. However, the commonly used metabolite ratios should still allow the detection of inborn errors of metabolism.
Gesehen am 28.12.2020